Enhanced Detection of DNA Viruses in the Cerebrospinal Fluid of Encephalitis Patients Using Metagenomic Next-Generation Sequencing - Manso, Carmen F.; Bibby, David F.; Mohamed, Hodan; Brown, David W. G.; Zuckerman, Mark; Mbisa, Jean L. (Frontiers in Microbiology, 2020)
The long and expanding list of viral pathogens associated with causing encephalitis confounds current diagnostic procedures, and in up to 50% of cases, the etiology remains undetermined. Sequence-agnostic metagenomic next-generation sequencing (mNGS) obviates the need to specify targets in advance and thus has great potential in encephalitis diagnostics. However, the low relative abundance of viral nucleic acids in clinical specimens poses a significant challenge. Our protocol employs two novel techniques to selectively remove human material at two stages, significantly increasing the representation of viral material. Our bioinformatic workflow using open source protein- and nucleotide sequence-matching software balances sensitivity and specificity in diagnosing and characterizing any DNA viruses present. A panel of 12 cerebrospinal fluid (CSFs) from encephalitis cases was retrospectively interrogated by mNGS, with concordant results in seven of nine samples with a definitive DNA virus diagnosis, and a different herpesvirus was identified in the other two. In two samples with an inconclusive diagnosis, DNA viruses were detected and in a virus-negative sample, no viruses were detected. This assay has the potential to detect DNA virus infections in cases of encephalitis of unknown etiology and to improve the current screening tests by identifying new and emerging agents.